Effectiveness of Acacia Wood Charcoal and Coconut Shell Analysis in Reducing Concentrations of Cr (VI) Pollution from Industrial Waste Using Adsorption Method at Laboratory Scale - Sholichin, Moh.; Ismuyanto , Bambang; Saptati N.H , AS. Dwi (Fakultas Teknik, Universitas Brawijaya, 2023)
Controlling the concentration of Cr(VI) in industrial wastewater is imperative to adhere to environmental quality standards and mitigate the risk of polluting river waters, ensuring the safety of living organisms and public health. Acacia wood charcoal and coconut shell charcoal have emerged as effective adsorbents capable of reducing Cr(VI) levels. This research seeks to identify the optimal adsorption pH and evaluate the impact of initial adsorbate concentration on Cr(VI) removal, comparing the efficacy of acacia wood charcoal and coconut shell charcoal. The study systematically manipulated process variables, encompassing 2, 4, and 6 pH levels and adsorbate concentrations of 30, 40, and 50 ppm. Charcoal characterization techniques, such as XRF, FTIR, and SNI, were employed alongside analyzing Cr(VI) levels utilizing UV-visible spectrophotometry. Results elucidated that coconut shell charcoal exhibited a higher percentage removal of Cr(VI) at concentrations of 30% (41%), 40% (38%), and 50 ppm (31%), outperforming acacia wood charcoal, which displayed removal percentages of 16%, 14%, and 7%, respectively. Consequently, the research underscores the superior efficacy of coconut shell charcoal in Cr(VI) removal compared to acacia wood charcoal under the specified conditions. The findings contribute valuable insights to optimizing adsorption processes for industrial wastewater treatment, promoting sustainable practices and environmental stewardship.